2011
DOI: 10.1007/s13762-011-0005-7
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of amide using Bacillus sp.: isolation strategy, strain characteristics and enzyme immobilization

Abstract: Amidase hydrolases/acyltransferases are of considerable industrial interest due to potential applications in the production of useful hydroxamic acids. The test strain, capable of acetamide degradation, was isolated by an enrichment technique with acetamide as sole source of nitrogen. Based on morphology, physiological tests and biochemical tests, this isolate was identified as Bacillus sp. and on the basis of 16S Ribosomal ribonucleic acid sequence, a phylogenetic tree was drawn and was identified as Bacillus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Bioaugmentation has been used to promote the start-up of a reactor, to protect the existing microbial community against adverse effects and to accelerate the removal of xenobiotics as a promising strategy for wastewater treatment Abdulsalam et al 2011;Sogani et al 2012). Wang et al (2002) studied the bioaugmentation for the removal of quinoline in coke plant wastewater by inoculating a quinoline-degrading bacterium Burkholderia pickettii in an anaerobic-anoxic-oxic system and found that bioaugmentation was an efficient strategy for increasing the removal of recalcitrant compounds from industrial wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…Bioaugmentation has been used to promote the start-up of a reactor, to protect the existing microbial community against adverse effects and to accelerate the removal of xenobiotics as a promising strategy for wastewater treatment Abdulsalam et al 2011;Sogani et al 2012). Wang et al (2002) studied the bioaugmentation for the removal of quinoline in coke plant wastewater by inoculating a quinoline-degrading bacterium Burkholderia pickettii in an anaerobic-anoxic-oxic system and found that bioaugmentation was an efficient strategy for increasing the removal of recalcitrant compounds from industrial wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…Enzyme immobilization has been studied and utilized to overcome these problems. [8][9][10][11] The enzyme immobilization is to entrap the enzymes in a semi-permeable supports, which prevents the enzyme from leaving while allowing substrates and products to pass through. 12 Immobilized enzymes typically exhibit greater stability and enzymatic activity over a broad range of pH and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…About degradation function Bacillus sp., most come from the polluted soil [11,12] , and some came from sediment [13] and water pollution [14] . Bacillus species are attractive industrial organisms not only because of their high growth rates leading to short fermentation cycle times, but also the spore-forming can resist many adverse environments.…”
Section: Discussionmentioning
confidence: 99%